Pengaruh Social Media Marketing terhadap Purchase Decision melalui Brand Trust: Studi Kasus pada Produk SKECHERS di Indonesia - Christian Sumarto; Sularsih Anggarawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
SKECHERS is a popular brand in Indonesian market, offering a diverse range of products for lifestyle and sport needs. The brand features hundreds of shoe models with attractive designs, along with hats, bags, sandals, clothes, and sports equipment. With the development of the internet and the prevalence of social media, this research aims to examine the influence of social media marketing on purchase decisions, with brand trust as a mediating variable, specifically for SKECHERS products in Indonesia. The research was conducted online, and data were collected by distributing questionnaires through Google Forms. The sampling technique employed was purposive sampling, with a total of 257 respondents. The analysis technique used was Structural Equation Modeling (SEM) based on components, utilizing Partial Least Squares (PLS) as the analytical tool. The results of hypothesis testing from the research indicate partial mediation, where social media marketing has a significant and positive influence on purchase decisions. Additionally, social media marketing also affects purchase decisions through brand trust.